Inflammatory Response Plays a Role in Innate Immunity: A Narrative Literature Review - Rara Inggarsih; Hidayat, Rachmat (HM Publisher, 2023)
The inflammatory response is the rapid initiation and interplay of humoral (dissolved in the blood) and cellular systems designed to limit the degree of tissue damage, destroy infectious microorganisms, initiate an adaptive immune response, and initiate the healing process. This review aimed to comprehensively describe the role of the inflammatory response in innate immunity. Three key plasma protein systems are essential for an effective inflammatory response. These are the complement system, clotting system, and kinin system. Although each system has a unique role in inflammation, they also share many similarities. Each system consists of several proteins in the blood. To prevent activation in unnecessary situations, each protein is normally in an inactive form. Some proteins are enzymes that circulate in an inactive form as proenzymes. Each system contains several proteins that can be activated at the start of inflammation. Cells of the innate and acquired immune systems are recruited and activated by biochemical mediators produced at sites of cell damage. These molecules originate from destroyed or damaged cells, contaminating microbes, activation of plasma protein systems, or secretion by other cells of the innate or acquired immune system. Activation may result in the cell acquiring a function essential for the inflammatory response or inducing the release of additional cellular products that promote inflammation, or both. In conclusion, inflammatory cells and various protein systems (complement, kinin, and clotting), together with the substances they produce, act at the site of tissue injury to limit the extent of damage, kill microorganisms, and remove debris in preparation for healing: tissue regeneration or repair.